Effect of hydro-priming and halo-priming on seed quality of faba bean varieties - ZEMET ALEMU CHANIE; R.P.S. TOMER; AMARE AYALE (Seed Research, 2026)
Farmers and researchers have recognized that poor crop establishment is a major constaint for crop production. Effect of seed priming treatments an physiological seed quality and seed health of faba bean varieties was investigated. The experiment was laid out with priming treatment (i.e. unprimed, 6, 12, 18 and 24 hrs with water and with KH,PO, at 0.5% solution for 12 hrs) and faba bean varieties (i.e.CS20DK, Gachena and Moti) in CRD factorial arrangement with four replications. The laboratory and green house results field experiements revealed significant differences at (P<0.001) for standard germination percentage, field emergence index, shoot length, seedling dry weight, vigour index I and II, speed of germination and electrical conductivity. However, halo-priming improved all seed vigour parameters except seedling dry weight, electrical conductivity and field emergence index for CS20DK did improve root length (17.73 cm) for Moti and had improved electrical conductivity (87.99 µscm-1g-1) and field emergence index (27.77%) for Gachena variety. Improvement made by hydro-priming was better than unprimed seed. The seed health status showed that incedence of Rhizopus sp. was higher among primed seeds. The present study concluded that 12h hydro-priming can set up economical benefit of faba bean growing farmers under field conditions.